Characteristics and outcome of influenza-associated encephalopathy/encephalitis among children in a tertiary pediatric hospital in Italy, 2017–2019 - Mastrolia, Maria Vincenza; Rubino, Chiara; Resti, Massimo; Trapani, Sandra; Galli, Luisa (BMC infectious diseases, 2019)
Influenza is the most frequent cause of acute upper respiratory tract infections during winter season. Although rare, neurological manifestations are known to occur during influenza infection and approximatively three-quarters of cases are in children. In this study, we aimed to characterize the burden and clinical spectrum of influenza-associated encephalopathy and encephalitis in children admitted at a tertiary pediatric hospital in Italy over two influenza seasons (2017-2019). We retrospectively analyzed clinical, laboratory, instrumental data and outcome of patients discharged with ICD9-CM 487.0 code. Fifteen children (13.1% of those discharged with a diagnosis of influenza infection in the study period), had influenza-associated central nervous system (CNS) manifestations. Eight patients (53.3%) were diagnosed as influenza encephalitis, 7 (46.7%) as influenza encephalopathy. Median age was 27 months. In children under 2 years of age (40% of all cases) altered consciousness was the most frequent neurological manifestation while respiratory symptoms were present at admission in all cases. Younger children also required intensive care support more frequently. Five subjects (33.3%) presented comorbidity. None of the patients had received seasonal influenza vaccination. The median time from onset of respiratory signs to onset of neurological manifestations was 24 h. Cerebrospinal fluid (CSF) analysis was normal in most patients and polymerase chain reaction for influenza virus RNA on CSF, when performed, was negative in all samples. Neuroradiological investigations, performed in 5 children, reported cortical and subcortical white matter signal alterations. Oseltamivir was administered only in 2 cases. Fourteen patients recovered without sequelae, and only a 2-year-old girl had minimal impairment in fine motor skills at discharge. All children presenting acute neurological features during influenza season should be evaluated for influenza-associated CNS complications even if the respiratory involvement is mild. Absence of underlying diseases or other risk factors are not protective factors against CNS influenza-associated complications. The lack of CSF pleocytosis does not exclude CNS involvement. Children under 2 years of age are at higher risk of requiring intensive care support.